Concept "city" in the context of interdisciplinary research - Machulin, L. I. (НТУ "ХПІ", 2016)
The article considers the interpretation of the concept "city" as a product of man’s activity in works of historians and sociologists, economists and urbanologists, philosophers and ecologists. The author pays special attention at the statement about the role of a city, its spheres, levels, cultures, and subcultures. The article proves the necessity of the synthesis of philosophical understanding of a city itself as an object, the concept "city", and factors of development of cities in different time and in different countries.

Розглядається питання трактовки поняття "місто" як продукта людської діяльності істориками та соціологами, економістами і урбанологами, філософами і екологами. Приділено увагу твердженням про призначення міста, його сфер, рівней, культур і субкультур. Доведено необхідність синтезу філософського розуміння самого міста, як об’єкта, поняття "місто", факторів розвитку міст в різний час і в різних державах
Поняття "місто" у площіні міждисциплінарних досліджень
Keywords: transformation of a city; philosophical understanding; civilization; social-economical space; трансформація міста; філософське розуміння